Implementasi Node MCU Sebagai Serial Komunikasi dengan Arduino Uno pada Smart Shopping Trolley - Yuliani, Livia Ayudia; Nurpulaela, Lela; Latifa, Ulinnuha (P3M Politeknik Negeri Banjarmasin, 2021)
Currently, there are many buyers who use the offline selling concept, so we often see long queues at su-permarkets. The queue is due to the length of time a chasier scans the price of each producs in the shop-ping cart. However, people always complain when doing the buying process at supermarkets. The public regretted the long queue process when making payment transaction at the cashier. This results in the length of the waiting time increasing according to the length of the queue. So, to be able to overcome this problem is to use internet of things which aims to facilitate the client in the process of purchasing a prod-uct. The internet of things device or component as an internet module is NodeMCU V2 AMINCA. The measurement method used is Quality of Service by using the assistance of the Wireshark application. Val-ue of throughput, packet loss, latency, and jitter obtained is 2229 bit/s, 0% packets, 25,284 seconds, 0,050 ms with category of zero throughput index (bad) and index four for packet loss, latency, and jitter.